Growth in early life and physical and intellectual development at school age: a cohort study. Issue 8 (11th February 2019) - Li, Chao; Zeng, Lingxia; Wang, Duolao; Allen, Stephen; Jaffar, Shabbar; Zhou, Jing; Chen, Tao; Watson, Victoria; Yan, Hong
Abstract: The associations between growth during early life and subsequent cognitive development and physical outcomes are not widely known in low-resource settings. We examined postnatal weight and height gain through early life and related these measurements to the nutritional status and intellectual development of the same children when they were between 7 and 9 years old. Mothers had enrolled in an randomised controlled trial to evaluate the effect of prenatal micronutrient supplementation on birth weight. Their children were born in 2004, their height and weight were measured at 6, 12, 18 and 24 months of age and were followed up between October 2012 and September 2013 (at ages 7–9 years, n 650). Height-for-age, weight-for-age and BMI-for-age were used to describe the nutritional status, and the Wechsler Intelligence Scale for Children fourth edition was used to measure the intellectual function. Multilevel linear and logistic modelling was used to estimate the association between early growth and subsequent growth and intellectual function. After adjustment, weight gain from 6 to 12 months of age was associated with Full-scale Intelligence Quotient, Verbal Comprehension Index, Working Memory Index and Perceptual Reasoning Index. Weight gain during early life was associated with subsequent nutritional status. For every 1 kg increase in weight during the 0- to 6-month period, the OR for underweight, thinness and stunting at 7–9 years of age were 0·19 (95 % CI 0·09, 0·37), 0·34 (95 % CI 0·19, 0·59) and 0·40 (95 % CI 0·19, 0·83), respectively. Weight gain during the periods of 6–12 months of age and 18–24 months of age was also associated with a lower risk of being underweight. Weight gain during early life was associated with better growth outcomes and improved intellectual development in young school-aged children.